Pelatihan Peningkatan Kecakapan Berbahasa Inggris untuk Siswa Sekolah Menengah Kejuruan - Pratiwi, Nindyah; Murtini, Mukti (Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract This article deals with training activities aimed at improving English language proficiency of high school students (SMK). This training is designed to help students master the English language skills necessary in the world of work, especially in the context of business and professional communication. The methods used in this training include simulation, role-playing, and the use of interactive media to ensure the active involvement of students. The training results showed an improvement in students' ability to communicate in English, both orally and in writing. Keywords: Training, English, Vocational High Schools, and language proficiency